University Sports at UFOP (2012 - 2018) - Renato Lopes Moreira; Rui Manuel Proença de Campos Garcia; Paulo Lanes Lobato (Universidade Salgado de Oliveira, 2020)
Ouro Preto Federal University (UFOP) is one of the few universities in Brazil and the only one in Minas Gerais that maintains Physical Education as an obligatory discipline in its curriculum even after the 9.394 / 96 Law was approval, which made the discipline optional in college. Based on that, combined with projects and programs offered by the university, competitive sports within UFOP was created in 2010, regularly participating in university and non-university competitions since then. This study aimed to analyze the management of college sports at UFOP from the perspective of athletes, analyzing from their point of view the entire context existing at the University, later confronting these views via SWOT analysis, seeking to obtain answers to the questions raised in it. This study is of a qualitative, exploratory, and applied nature, and used the analysis of documentary sources and the application of questionnaires with athletes from university teams to collect the desired information. 124 questionnaires were answered, and this answer was interpreted through the SWOT analysis, presenting 8 opportunities, 7 threats, 8 strengths, and 11 weaknesses for the management of the college sports at UFOP. These results were analyzed and allow us to conclude that the potential of the sport of UFOP is notorious, but it is necessary and urgent that the university create help and support mechanisms to better structure the sport of competition within it.